"Selling the Dead": More dignified options needed to assist widows in post-disaster recovery after Typhoon Haiyan. (September 2020) - Su, Yvonne; Mangada, Ladylyn
Abstract: When Typhoon Haiyan struck the Philippines on November 8th, 2013, it took the lives of over 6300 people. Many of those who died were men who did not evacuate to protect their homes. As a result, widowhood was a significant and devastating consequence of Haiyan, but widows were also one of the most underserved vulnerable populations in the aftermath. Drawing on interviews with 15 widows who lost their husbands during Haiyan, this case report argues that the burial assistance program did not prioritize the dignity of those who have died and the widows who must claim the assistance. Our fieldwork uncovered three main issues with the burial assistance program: 1) mass graves resulted in the burial of many unidentified bodies, 2) bureaucratic challenges complicated the process, and 3) widows felt like they were " selling the dead " when claiming the funds. Overall, many of the widows felt the program did not consider their vulnerability and severe needs. In the end, despite this being the only form of humanitarian assistance targeted at widows, the majority of the widows we interviewed were unable to access it. We argue that these issues stem from the absence of a survivor-centered approach to decision-making and program design. We recommend the creation of a streamlined one-stop shop for burial assistance applications and claims at the local barangay level. In addition, we argue that more dignified options are needed to assist widows in post-disaster recovery so they do not feel like they are "selling the dead" in the case of Haiyan's burial assistance program.